PENGUJIAN LEMARI PENGERING KOPRA TIPE KABINET SISTEM HYBRID (SOLAR DRYER PLAT DATAR – HEATER) - FERDINAN PUAY; Verdy A. Koehuan; Adi Y. Tobe (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2025)
Along with the development of drying process technology, solar energy is used as an energy source whose availability will never run out and this energy can also be used as alternative energy which will be converted into electrical energy, drying It is hoped that using a solar dryer will be able to produce high quality copra and be a form of saving on electrical energy usage. After testing 3 times using direct heating from a solar energy source and 2 variations of heater heating elements with a power of 110 watts and 260 watts respectively, the most efficient results were obtained, namely in testing using a 100 watt heating element on the second day. During the 4 hours of testing, the water content value that came out of the coconut meat reached 22.49% compared to testing on the first and third days. This is caused by changes in environmental temperature (Tl) and environmental humidity (Hl) which affect the temperature conditions in the equipment drying room. For testing using 260 watts of power, the results were not efficient because it has very high power so that the energy stored in the battery cannot work during the 4 hours of drying time.